Self-efficacy beliefs and young people's political participation - Bjarki Þór Grönfeldt 1994- (2016)
Political efficacy is one of the strongest predictors of adults’ political participation, but it has been less studied among young people. General self-efficacy has been considered a possible causal factor for young people to engage in politics. These constructs, in addition to young people’s participation in the so called “social media revolutions” (SMR), an Internet phenomenon in Iceland, were examined. An online survey was posted on social media and emailed to students at a large university in Iceland. A total of 459 participants (60.7% female, 39.3% male) between the ages of 18 and 31 (M = 23.9, SD = 3.5) completed the survey. Both general and political efficacy were associated with political participation, but mediation analysis reviled that the relationship between general self-efficacy and political participation was mediated through political efficacy. Logistic regression analysis showed that political efficacy predicted SMR-participation, but general self-efficacy did not. Furthermore, SMR- participants participated more actively in politics than did non-participants. The results underline the importance of political efficacy for political participation among young people, but indicate that the effects of general self-efficacy are minimal. Pólitísk sjálfstiltrú er einn af sterkustu forspárþáttum stjórnmálaþátttöku á meðal fullorðinna, en það samband hefur verið minna rannsakað á meðal ungs fólks. Almenn sjálfstiltrú hefur verið talin mögulegur áhrifaþáttur á stjórnmálaþátttöku ungs fólks. Þessi hugtök, auk þátttöku í „byltingum“ á samfélagsmiðlum á Íslandi, voru rannsökuð. Könnun var send út á samfélagsmiðlum og til nemenda íslensks háskóla. Samtals tóku 459 manns þátt (60.7% konur, 39.3% karlar) á aldrinum 18 – 31 árs (M = 23.9, SD = 3.5). Niðurstöðurnar sýndu að bæði pólitísk og almenn sjálfstiltrú höfðu tengsl við stjórnmálaþátttöku, en sambandi almennrar sjálfstiltrúar og stjórnmálaþátttöku var miðlað í gegnum pólitíska ...